Response of the Ubiquitous Pelagic Diatom Thalassiosira weissflogii to Darkness and Anoxia - Kamp, Anja (Public Library of Science, 2013)
Thalassiosira weissflogii, an abundant, nitrate-storing, bloom-forming diatom in the world’s oceans, can use its intracellular nitrate pool for dissimilatory nitrate reduction to ammonium (DNRA) after sudden shifts to darkness and anoxia, most likely as a survival mechanism. T. weissflogii cells that stored 4 mM (15)N-nitrate consumed 1.15 (±0.25) fmol NO(3) (-) cell(-1) h(-1) and simultaneously produced 1.57 (±0.21) fmol (15)NH(4) (+) cell(-1) h(-1) during the first 2 hours of dark/anoxic conditions. Ammonium produced from intracellular nitrate was excreted by the cells, indicating a dissimilatory rather than assimilatory pathway. Nitrite and the greenhouse gas nitrous oxide were produced at rates 2-3 orders of magnitude lower than the ammonium production rate. While DNRA activity was restricted to the first few hours of darkness and anoxia, the subsequent degradation of photopigments took weeks to months, supporting the earlier finding that diatoms resume photosynthesis even after extended exposure to darkness and anoxia. Considering the high global abundance of T. weissflogii, its production of ammonium and nitrous oxide might be of ecological importance for oceanic oxygen minimum zones and the atmosphere, respectively.